New Hydrangeas for North and Central Florida: Bigleaf and Mountain Hydrangeas - Gary W. Knox (EDIS)
ENH-1034, a 5-page fact sheet by Gary W. Knox, describes new cultivars of this shade-preferring shrub which has re-emerged as an important garden plant, providing explanation and history of reflowering cultivars, as well as other notable non-reflowering cultivars that are being marketed in the U.S. Published by the UF Environmental Horticulture Department, March 2006.